Deteksi fenomena "market shock" di Indonesia dalam isu likuidasi perbankan AS - Handel Benedicto Mangero; Reno Kirauhe (Riset Akuntansi dan Portofolio Investasi, 2023)
Investor reactions in the capital market are often triggered by several factors. One of the most dominant factors influencing the psychology of investors is information on issues related to economic events. The aim of this study is to examine the daily closing prices of market indices within a confidence interval. This study finds that most of the market indices tend to be less than the lower limit except for the IDXTRANS. These findings imply that the issue of liquidation of several banking businesses in the US tends to result in market shocks in Indonesia, especially during the observation period.